International Perspectives on Vietnam's Educational Reform - THI MAI PHUONG LE (International Journal of Multidisciplinary Research and Studies, 2023)
The purpose of "cultivating people" is an admirable and ambitious one. Learning and research are crucial to the growth of every civilization. Education efficiently serves the socioeconomic development goals of each nation and ethnic group by producing well-informed, competent, and healthy members of society. Development in education and training is now seen as a key priority by governments throughout the world, including Vietnam, which sees it as an investment in the future of its citizens. Vietnam's education system faces many challenges as a result of international integration. This is because our system continues to place too much emphasis on knowledge transmission rather than the quality and capacity development of learners; the quality of our teaching and administrative staff is not uniform; and our infrastructure system has not yet been fully developed. To address the demands of its inhabitants while it undergoes internationalization, Vietnam's educational system has to be developed.